2018
DOI: 10.1186/s42358-018-0033-9
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the effects of strength training in patients with fibromyalgia: clinical outcomes and design considerations

Abstract: Background: Fibromyalgia (FM) is characterized by chronic and generalized musculoskeletal pain. There is currently no cure for FM, but palliative treatments are available. One type of treatment is strength training (ST). However, there is a need for more information on optimal training protocols, intensity, and volume needed to improve symptoms. The aim of this study was to analyze the effects of ST in the treatment of FM through a systematic review of experimental research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 58 publications
1
40
0
Order By: Relevance
“…Studies investigating COVID-19 patients found a high level of post-traumatic stress and depressive symptoms in comparison with non-infected people ( Vindegaard and Eriksen Benros, 2020 ). In this regard, there are consistent evidence that RT is associated with improvements in depression ( Gordon et al, 2018 ), anxiety ( Gordon et al, 2017 ), and sleep disorders ( Kovacevic et al, 2018 ), including patients with chronic diseases ( Ferreira et al, 2020 ) and during rehabilitation ( McCartney, 1998 ; Vincent and Vincent, 2012 ; Chan and Cheema, 2016 ; Andrade et al, 2018 ; Seguro et al, 2019 ). The potential benefits of RT for COVID-19 patients are illustrated in Figure 1 .…”
Section: Practical Recommendationsmentioning
confidence: 92%
“…Studies investigating COVID-19 patients found a high level of post-traumatic stress and depressive symptoms in comparison with non-infected people ( Vindegaard and Eriksen Benros, 2020 ). In this regard, there are consistent evidence that RT is associated with improvements in depression ( Gordon et al, 2018 ), anxiety ( Gordon et al, 2017 ), and sleep disorders ( Kovacevic et al, 2018 ), including patients with chronic diseases ( Ferreira et al, 2020 ) and during rehabilitation ( McCartney, 1998 ; Vincent and Vincent, 2012 ; Chan and Cheema, 2016 ; Andrade et al, 2018 ; Seguro et al, 2019 ). The potential benefits of RT for COVID-19 patients are illustrated in Figure 1 .…”
Section: Practical Recommendationsmentioning
confidence: 92%
“…Especially with respect to depression, exercise has been studied as a potential nonpharmacological treatment in several populations [ 29 , 30 ]. Regarding mood, physical activity at home should be seen as a distractor for older adults.…”
mentioning
confidence: 99%
“…36 The current evidence demonstrates that strength training is beneficial and can treat fibromyalgia, bringing positive results through reduction of pain, number of tender points, depression, and anxiety. 37,38 Our study demonstrated that exergaming is a useful tool for improving muscle strength in lower limbs by increasing the peak torque. Kisiel-Sajewicz et al 39 reported that parameters such as MVIC can provide information on brain dynamics, with the motor cortex, corticospinal, supraspinal, propriospinal, motoneuron, and motor axon areas having a central function for the muscle contraction.…”
Section: Discussionmentioning
confidence: 67%